PENGARUH PEMBERIAN HUKUMAN TERHADAP KEDISIPLINAN PESERTA DIDIK - Nurlita Maulida; Mira Mirawati; Wawan Syahiril Anwar (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2020)
THE EFFECT OF PUNISHMENT OF THE DISCIPLINE OF STUDENTSThis research uses a causal quantitative research design. The purpose of this research is to determine the effect of punishment on the discipline of students. This research was conducted at Panaragan 1 Primary School in class V odd semester 2019/2020 school year. The population in the study amounted to 108 students and samples taken as many as 52 students were obtained using the Taro Yamane formula. The results showed that there was an effect of giving penalties on student discipline, indicated by statistical analysis which resulted in a correlation coefficient of 0.485. Data analysis techniques with regression analysis and path coefficients produce a model of influence expressed in the form of a regression equation that is Ŷ = 63.07 + 0.35X, with a Fcount value of 15.34 greater than Ftable with a significance level of 0.05 of 4, 03 and the contribution based on the results of the study amounted to 23.52% while 76.48% is influenced by other factors, it can be concluded that there is a positive and significant effect on the discipline of the fifth grade students of Panaragan State Elementary School 1 Odd Semester in the 2019/2020 school year